Cardona Zuleta, L. M. (2016): La culebra sigue viva: miedo y política - Duque Daza, Javier (Reflexión Política, 2018)
Libro: Cardona Zuleta, L. M. (2016). La culebra sigue viva: miedo y política. Medellín: Universidad Nacional de Colombia.